Development of Android-Based Interactive Learning Media on Computer Assembly Material with the ADDIE Model Approach: case study : SMK Negeri 1 Lolayan - Jemmy Pakaja; Hermila A.; Alfito Paputungan (Politeknik Negeri Cilacap, 2024)
This study raises the title of the development of android-based interactive learning media on computer assembly material at SMK Negeri 1 Lolayan. Based on the observations and interviews, several problems were found in learning computer assembly material, including teachers still using PowerPoint learning media that is only text-based. During the practicum, one of the computers used was damaged. This is due to limited knowledge and inadequate facilities, resulting in teachers' lack of innovation and creativity in developing learning media, which makes it difficult for students to understand the material. This study aims to develop android-based interactive learning media on Computer Assembly material for class X TKJ students at SMK Negeri 1 Lolayan and test the feasibility of interactive learning media through material and media expert feasibility tests and determine the practicality of learning media through respondent trials (students/users). The research method used is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The results of this study were obtained from feasibility testing by material experts, who obtained an average value of ‘138’ with the criteria ‘Very Feasible.’ The results of feasibility testing by media experts obtained an average value of ‘120’ with the criteria ‘very Feasible,’ and the results of testing student response responses obtained an average value of ‘101’ with the criteria ‘Very Feasible’. The results showed that Android-based interactive learning media is feasible to use as an alternative to learning computer assembly